2004
DOI: 10.1021/bi049589v
|View full text |Cite
|
Sign up to set email alerts
|

A Calmodulin-Regulated Protein Kinase Linked to Neuron Survival Is a Substrate for the Calmodulin-Regulated Death-Associated Protein Kinase

Abstract: Death-associated protein kinase (DAPK) is a calmodulin (CaM)-regulated protein kinase and a drug-discovery target for neurodegenerative diseases. However, a protein substrate relevant to neuronal death had not been described. We identified human brain CaM-regulated protein kinase kinase (CaMKK), an enzyme key to neuronal survival, as the first relevant substrate protein by using a focused proteomics- and informatics-based approach that can be generalized to protein kinase open reading frames identified in geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 18 publications
(24 reference statements)
5
41
0
Order By: Relevance
“…Both proteins were found in immunoprecipitates from rat brain and kinetic analyses show that S6 is a DAPK substrate. Further, the amino acid sequence surrounding the site of phosphorylation in S6 by DAPK matches the pattern revealed by positional scanning peptide library screening for DAPK substrate preferences (21) and by the proteomics-based mapping of DAPK phosphorylation sites in protein substrates (8). Second, DAPK phosphorylates S6 in the context of the 40S ribosomal subunit at position Ser235, but does not phosphorylate S6 at any of the other four sites phosphorylated by previously discovered S6Ks.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Both proteins were found in immunoprecipitates from rat brain and kinetic analyses show that S6 is a DAPK substrate. Further, the amino acid sequence surrounding the site of phosphorylation in S6 by DAPK matches the pattern revealed by positional scanning peptide library screening for DAPK substrate preferences (21) and by the proteomics-based mapping of DAPK phosphorylation sites in protein substrates (8). Second, DAPK phosphorylates S6 in the context of the 40S ribosomal subunit at position Ser235, but does not phosphorylate S6 at any of the other four sites phosphorylated by previously discovered S6Ks.…”
Section: Discussionsupporting
confidence: 55%
“…Although these findings support the notion that calcium/calmodulin-regulated pathways affect the molecular mechanisms that influence synaptic plasticity (47,48), clearly, much remains to be done as a follow up to the novel finding reported here that DAPK is capable of regulating protein synthesis with a possible role in neuronal function. Regardless, the key findings reported here and previously (2,5,8) provide an emerging view of DAPK as a kinase potentially capable of selective modulation of neuronal homeostasis in rapid response to diverse stimuli, with apoptosis as one possible outcome that can be attenuated by targeted therapeutics in disease-relevant events.…”
Section: Discussionmentioning
confidence: 58%
“…It is possible that the previously identified DAPk substrate syntaxin-1A, a component of the v-SNARE complex, may be involved. 35 Notably, the CaM-dependent kinase kinase b (CaMKKb), another substrate of DAPk, 36 has been implicated in mediating autophagy induced by ionomycin and inducers of ER stress. 29 However, phosphorylation of CaMKKb by DAPk on Ser511 attenuates the former's CaM-dependent autophosphorylation, a step necessary for its activation, suggesting that DAPk actually inhibits CaMKK function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that DAPK1 phosphorylates diverse substrates via its kinase domain. These substrates include the MLC [19], beclin-1 [37,38], zipper-interacting protein kinase (ZIPK) [39,40], calmodulin-regulated protein kinase kinase (CaMKK) [41], and syntaxin-1A [42]. The requirement of DAPK catalytic activity for its proposed cell functions and the validation of protein kinases as therapeutic targets in human disease make the identification of substrates of DAPK1 in ischemia extremely important.…”
Section: Dapk1 and Its Kinase Activity In Ischemic Neuronal Deathmentioning
confidence: 99%